1995
DOI: 10.1080/01904169509365097
|View full text |Cite
|
Sign up to set email alerts
|

Source and mode of sulphur application on groundnut productivity

Abstract: The effectiveness of 20 kg/ha sulphur (S) of the S-containing compounds iron sulphate (FeSO 4 ), gypsum, phosphogypsum, elemental S, and pyrite on groundnut (Arachis hypogaea L.) productivity was determined for plants grown on calcareous soil in the field. Plants grown with S compared to those without S had increased plant height, number of flowers, nodule numbers and weight, higher dry matter, seed, haulm (leaves and stems), and oil yields; higher tissue concentrations of nitrogen (N), phosphorus (P), S, iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The maximum Ca content (0.53%) was found from the treatment of 30 kg S ha -1 and the minimum (0.48%) content was observed from control (Table 2). It was similar to the result of Singh et al (2007) who concluded that application of 30 kg S ha -1 as gypsum recorded significantly higher Ca content in potato. The interaction effects of P and S on Ca content was significant.…”
Section: Phosphorus Contentsupporting
confidence: 90%
See 1 more Smart Citation
“…The maximum Ca content (0.53%) was found from the treatment of 30 kg S ha -1 and the minimum (0.48%) content was observed from control (Table 2). It was similar to the result of Singh et al (2007) who concluded that application of 30 kg S ha -1 as gypsum recorded significantly higher Ca content in potato. The interaction effects of P and S on Ca content was significant.…”
Section: Phosphorus Contentsupporting
confidence: 90%
“…This might be due to synergistic effect of S on Ca. Singh et al (2007) found that in potato, there was a gradual increase in Ca uptake with increasing levels of S upto 30 kg ha -1 . The highest (551 mg pot -1 ) and lowest (107 mg pot -1 ) uptakes of Ca were recorded in P 60 S 30 and P 0 S 0 levels, respectively.…”
Section: Sulphur Uptakementioning
confidence: 95%
“…Chaubey et al (1993) found increases in N uptake by linseed grains and straw as a result of S application to the sandy loam soils. Singh and Chaudhari (1995) recorded higher concentrations of N in tissues of peanut plants grown on calcareous soils with applied S compared to those without S.…”
Section: Nitrogen Uptake By Cornmentioning
confidence: 86%